Investigating the Role of Excellent Model in the Competitive Market with Impact on The Economy - Asadi, Rahil (Journal of Economic Development, Environment and People, 2020)
Abstract. Nowadays, gaining competitive advantage depends on the organization’s capability to moving towards excellence and superiority in various dimensions. Creating competition with ethical principles means that, with scientific methods and strategic planning step towards strengthening the organization performance in the competitive market. There are many ways to gain the competitive market advantage and all that need to be appropriate and accordance with the cultural, political, human and structural conditions. Between all ways, one of the solutions that is more culturally, humane, and structurally appropriate to the organizational and the local business environment, and in practice, some organizations have proven it to be as a high-value or excellent and standard model, can name a model of E.F.Q.M (EUROPEAN, FOUNDATION, QUALITY, MANAGEMENT). Research methodology – This paper focuses on a conceptual analysis of the relations among establishing an excellence model in the organization and gaining competitive advantage. Here the EFQM excellence model is considered as a suitable framework for achieving the competitive advantage in the market for the organization. The revision of academic literature and logical analysis are the main methodological tools. Findings – The study shows that establishing competitive advantage foundations and excellence model in the organization and then evaluate and assessing them based on the components mentioned here, can achieve competitive advantage for the organization in the global scale, and in this sense, it is possible to define relationships and impact between each component of excellent model and those coming from the model on the competitive advantage.